Co-processing of the arrowroot-chitosan by spray drying - Yudi Wicaksono; Yuli Witono; Herlina .; Nuri . (Indonesian Journal of Pharmacy, 2010)
Starch is one of the most widely used excipient in the manufacture of solid dosage forms. One of few problems associated with starch is its poor flowability so  can’t  used  as  excipient  in  direct  compression  tablet.  The  purpose  of  these studies  was  to  develop  of  the  arrowroot  starch  for  use  as  excipient  in  direct compression  tablet.  The  arrowroot  starch  was  co-processing  with  chitosan  by spray  drying.  The  suspension  of  arrowroot  starch-chitosan  for  feed  in  spray drying were prepared with three different ratios (1:1, 2:1 and 3:1). The product of  co-processing  were  evaluated  for  morphology,  moisture  content,  viscosity, angle  of  repose,  flow  rate  of  granules,  bulk  density,  tapped  density  and  Carr’s index.  Results  showed  that  co-process  excipient  of  arrowroot  starch-chitosan have  spherical  in  shape,  moisture  content  in  the  range  of  4.70–5.10  % w/w, viscosity  in  the  range  of   1.77-2.17  mPas,  angle  of repose  was  found  to  be  < 380, flow rate of granules in the range of 1,5 – 4,0 g/s, bulk density in the range of  0.47-0.59 g/mL,  tapped  density  in  the  range of 0.59–0.79  g/mL  l and Carr’s index in the range of 19.03-25.08 %.Key words: arrowroot starch, co-process excipient, direct compression